STRUKTUR DAN POLA HUBUNGAN SOSIAL DALAM KOMUNITAS TOLOTANG BENTENG DI AMPARITA KAB. SIDRAP PROVINSI SUL-SEL - Maidin, Andi M.Rusbin (Jurnal Ilmiah Ecosystem, 2016)
This study examines the structure and patterns of social relationships in thecommunity Tolotang fort in the district Amparita Sidrap. The term Tolotangfortress consists of the word "Tolotang" and "Castle". Tolotang derived from theterm toriolota abbreviated to mean the people and riolota To once or ancestorslater shortened the name Tolotang and later became a confidence and trust.Community Tolotang Fortress is a community of people who have two elements,namely the elements of Islam and elements Tolotang, they recognize as the Godof Gods SeuwaE They and Sawerigading as Prophet m hey. And they have a holybook in the form of lontara-lontara, has pemmali-pemmali Tolotang Citadel ledby a "Uwatta" as the highest piumpinan, Uwatta position now held by Ir. HamkaMuin the 15th Founder's first Tolotang Fort La Panaungi, the central rite theyare at the Well Pakkewarue (hopefully safely), Pabbajueja wells and in thecemetery of La Panaungi. They also have Makkuraurang (drugs) as well asEngrekang.The approach used is qualitative with case study method by taking informantssebanak 21 by way of sampling snobal then made glittering narrative form. Theresults of this study indicate social structures are two-dimensional TolotangFort vertical and horizontal, and the pattern of social relations in the communityTolotang fortress there are two patterns of relationships that uwatta as aspiritual leader in the community trust Tolotang Fortress and uwatta as informalleaders in the community.